2013
DOI: 10.1021/es4012349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gaseous Oxidized Hg Measured by KCl-Coated Denuders, and Nylon and Cation Exchange Membranes

Abstract: The chemical compounds that make up gaseous oxidized mercury (GOM) in the atmosphere, and the reactions responsible for their formation, are not well understood. The limitations and uncertainties associated with the current method applied to measure these compounds, the KCl-coated denuder, are not known due to lack of calibration and testing. This study systematically compared the uptake of specific GOM compounds by KCl-coated denuders with that collected using nylon and cation exchange membranes in the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(223 citation statements)
references
References 45 publications
(124 reference statements)
11
211
1
Order By: Relevance
“…Consequently, GEM measurements at Cape Point, Cape Grim and Amsterdam Island are comparable to TGM measured at Troll research station. We caution, however, that recent studies have shown that the KCl-coated denuder in the Tekran speciation technique does not efficiently collect all GOM Huang et al, 2013;Ambrose et al, 2013). The bias between the TGM measurements at Troll research station and GEM measurements at all other stations can thus be larger.…”
Section: F Slemr Et Al: Comparison Of Mercury Concentrations Measurmentioning
confidence: 87%
“…Consequently, GEM measurements at Cape Point, Cape Grim and Amsterdam Island are comparable to TGM measured at Troll research station. We caution, however, that recent studies have shown that the KCl-coated denuder in the Tekran speciation technique does not efficiently collect all GOM Huang et al, 2013;Ambrose et al, 2013). The bias between the TGM measurements at Troll research station and GEM measurements at all other stations can thus be larger.…”
Section: F Slemr Et Al: Comparison Of Mercury Concentrations Measurmentioning
confidence: 87%
“…Recent field and laboratory intercomparisons suggested that the GOM measured by the Tekran system may be biased low by a factor of 1.6-10.6 times compared to recently developed methods using the Detector for Oxidized Hg Species (DOHGS), nylon membranes and cation exchange membranes, and the magnitude of bias can be influenced by the forms of GOM, ozone and relative humidity (Lyman et al, 2010;Huang et al, 2013;Gustin et al, 2013;Ambrose et al, 2013;McClure et al, 2014). A manual method similar to the Tekran 2537/1130/1135 system has also been deployed (Fu et al, 2012a;Zhang et al, 2015a).…”
Section: W Fu Et Al: Observations Of Atmospheric Mercury In Chinmentioning
confidence: 99%
“…8). This is especially valuable for the analysis of oxidized mercury species, as there is an ongoing discussion about an underestimation of concentrations due to limitations of the current measurement techniques (Lyman et al, 2010Ariya et al, 2015;Gustin et al, 2015;Huang and Gustin, 2015;Jaffe et al, 2014;McClure et al, 2014;Ambrose et al, 2013;Huang et al, 2013;Kos et al, 2013). Generally, the model error can be separated into three parts: the bias, which represents any systematic errors; the variance, which gives the variability around the mean value; and the covariance, which represents the correlation between model and observations (Solazzo and Galmarini, 2016).…”
Section: Model Evaluationmentioning
confidence: 99%